Database replication for disconnected operations with quasi real-time synchronization - Mucha, Rafal; Balis, Bartosz; Grigoras, Costin; Kitowski, Jacek (Computer Science, 2023)
Database replication is a way to improve system throughput or achieve high availability. In most cases, using an active-active replica architecture is efficient and easy to deploy. Such a system has CP properties (from the CAP theorem: Consistency, Availability and network Partition tolerance). Creating an AP (available and partition tolerant) system requires using multi-primary replication. This approach, because of many difficulties in implementation, is not widely used. However, deployment of CCDB (experiment conditions and calibration database) needs to be an AP system in two locations. This necessity became an inspiration to examine the state-of-the-art in this field and to test the available solutions. The tests performed evaluate the performance of the chosen replication tools: Bucardo and EDB Replication Server. They show that the tested tools can be successfully used for continuous synchronization of two independent database instances.